(untitled) (Sociología y tecnociencia, 2013)
The competition for talent and highly skilled migrants is increasingly the subject of discussion at international conferences. Skilled migration and brain drain have in fact been on the agenda to a varying extent for five decades. Yet despite the longevity of this preoccupation, scant attention has been paid to the role of the family, personal relationships, spousal employment and caring responsibilities, how these differ according to gender, and what impacts they have on policies designed to attract highly skilled migrants.